Palliative care in primary health care: scoping review - Eveline Treméa Justino; Maristel Kasper; Karen da Silva Santos; Rita de Cassia Quaglio; Cinira Magali Fortuna (Universidade de São Paulo, 2020)
Objective: to map the available evidence on the main topics investigated in palliative care in primary health care. Method: scoping review type study carried out in five databases, including original articles, based on the descriptors palliative care, palliative care at the end of life, terminal care, terminal state, primary health care and their respective acronyms and synonyms, totaling 18 publications. The extraction of data from primary studies was performed using an instrument produced by the authors and which allowed the construction of the categories presented. Results: 18 publications were included in this review. Among the most studied themes are the difficulties of the teams regarding the continuity of care in the health network; the importance of in-service education by the multidisciplinary team; professional unpreparedness; bioethics; the validation and application of scales for prognosis and care for some pathologies such as cancer and diabetes; among others. Conclusion: it became evident that palliative care in primary health care has been gradually developed, but it is necessary to consider the organization of primary health care and the social policies that support or weaken it, being considered a complex challenge.